Solar energy storing rock-bed to heat an agricultural greenhouse. (15th February 2019) - Gourdo, L.; Fatnassi, H.; Tiskatine, R.; Wifaya, A.; Demrati, H.; Aharoune, A.; Bouirden, L.
Abstract: The quality requirements of crops, particularly for export, are causing more and more Moroccan producers to consider heating their greenhouses. As the heating costs by conventional energy sources (coal, oil and natural gas) is too high, especially for developing countries, the use of renewable energy technologies and systems to heat the greenhouses have gained much attention in recent years. In this context, to maintain the optimum growth environment for plants, a solar energy storing rock-bed has been used to heat the ambient air inside a canarian type greenhouse. This system stores excess heat from the greenhouse during the day and restitutes it at night. The results of experimental measurements of the climatic parameters show that air temperature inside the greenhouse equipped with rock-bed is on average 3 °C higher than inside the conventional greenhouse during the night and 1.9 °C lower during the day. As the greenhouse equipped with the solar energy storing system was cooled down during the day and heated-up at night, its relative humidity was naturally higher during the day and lower at night. In addition, this system has a positive effect on the tomato yield, which has been improved by 22% compared to the conventional greenhouse. Highlights: Study of an innovative and economic system for heating an agricultural greenhouse. Rocks as a heat storage medium is an effective solution to heat greenhouses. Solar rock-bed system is a profitable heating greenhouse system. Tomato yield can be improved by 22% compared to the conventional greenhouse.